Correlation between oxygen saturation of patient and severity index of Covid 19 pneumonia on CT - Fatima, Nimra; Saad Ahmed Khokhar; Rai Muhammad Farooq Ur Rehman (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the correlation between capillary blood oxygen saturation and computerised tomography severity index in patients with coronavirus disease-2019 pneumonia. Method: The cross-sectional analytical study was conducted at the coronavirus disease-2019 ward of Nishtar Medical University and Hospital, Multan, Pakistan, June 1, 2020, to June 1, 2021. At the time of admission, capillary oxygen saturation of all patients was measured. Pulmonary computerised tomography scans were then performed, and computerised tomography severity index was calculated. Data was analysed using SPSS 18. Results: Of the 170 patients, 90 (52.9%) were males and 80(47%) were females. The overall mean age of the sample was 56.32±12.45 years. At the time of admission, the mean oxygen saturation was 88.9±6.53% and the mean severity index was 15.01±7.79. Overall, 22(12.9%) patients had hypoxia and the severity index reading was significantly high in these patients (p=0.001). Chronic obstructive pulmonary disease, hypertension and diabetes were significantly related to reduced blood oxygen saturation (p<0.05). Patients with hypertension had significantly raised computerised tomography scores. A significant inverse correlation was found between capillary oxygen saturation and computerised tomography severity index (p<0.01). Conclusions: A significant inverse correlation was found between capillary oxygen saturation and computerised tomography severity index. Underlying comorbidities also affected the severity index. Key Words: Covid-19, Hypoxia, Capillary oxygen saturation, Chest CT, CT severity index.